2022
DOI: 10.14739/2310-1210.2022.5.261327
|View full text |Cite
|
Sign up to set email alerts
|

Key astroglial markers in human liver cirrhosis of different degree: immunohistochemical study

Abstract: The aim of the study – determining the immunohistochemical levels of the GFAP, GS and AQP4 in different regions of the human brain in the conditions of liver cirrhosis of different degree. Materials and methods. The study was performed on sectional material of 90 patients who suffered during lifetime from liver non-alcoholic cirrhosis of classes A (n = 30, group “A”), B (n = 30, group “B”) and C (n = 30, group “C”) according to Child–Pugh classification, including 59 (65.55 %) cases with clinical symptoms of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…It should be noted that NECs in the studied SVZs and hypothetical alternative neurogenic niches morphologically correspond to the proliferative NSCs described by other researchers [15,24]. Thus, we assume that revealed growth of Nestin+, CD44+, GS+ expression in astrocyte-like cells of SVZs and hypothetical alternative neurogenic niches during compensated and subcompensated cirrhosis is due to the activation of astrocytogenesis programs in response to widespread dysmetabolic astrodystrophy and astrocyte loss developing in patients with cirrhosis [1].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It should be noted that NECs in the studied SVZs and hypothetical alternative neurogenic niches morphologically correspond to the proliferative NSCs described by other researchers [15,24]. Thus, we assume that revealed growth of Nestin+, CD44+, GS+ expression in astrocyte-like cells of SVZs and hypothetical alternative neurogenic niches during compensated and subcompensated cirrhosis is due to the activation of astrocytogenesis programs in response to widespread dysmetabolic astrodystrophy and astrocyte loss developing in patients with cirrhosis [1].…”
Section: Discussionsupporting
confidence: 78%
“…We found that with the progression of cirrhosis, astrocytes of SVZs and SGZ DG significantly increases GS expression, and this sharply decrease in elderly patient's SVZ with decompensated cirrhosis, as well as in other brain regions [1]. This most likely indicates an adaptive increase in GS synthesis by periventricular, including fibrous astrocytes in response to high levels of ammonia in the brain tissue, which is accompanied by the activation of neurogenesis programs in niches and an increased Nestin level.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Sepsis-associated encephalopathy (SAE), which develops under these conditions, has a complex mechanism, since in addition to the neurotoxic effect of systemic infection, its decay products, pathogenassociated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), it is complicated by a pronounced neurotoxic effect of hyperammonemia, which follows a decrease in the detoxifying capacity of the liver. It is evidenced that during chronic liver failure in liver cirrhosis a morphotypical remodeling astroglia occurs with the appearance of the so-called Alzheimer type 2 astrocytes and changes in the expression of its specific proteins, such as glial fibrillar acidic protein (GFAP), glutamine synthetase (GS) and aquaporin-4 (AQP4) [4,5]. Also, in patients with chronic and acute liver failure, the level of intracerebral ammonia increases, which was confirmed using neuroimaging methods [6].…”
mentioning
confidence: 86%